Praxis of University-School Partnerships and Collaborations to Foster Information, Knowledge and Technology Exchange in Tanzania - Kahangwa, George Leonard (University of Dar es Salaam Library Journal, 2025)
This paper examines the collaboration between universities and primary and secondary schools in Tanzania, the reasons behind these partnerships, and the outcomes of such collaborations. The paper draws from McQuaid’s theory of organisational partnerships, which assumes that partnerships have purpose, actors, structures, and benefits. A multi-site case study of public and private universities and schools engaged in partnerships was employed. The study used purposive sampling to generate data by targeting partnering universities and schools. The data were collected through interviews with coordinators of these partnerships in their respective organisations, as well as open-ended questionnaires administered to university and basic education students engaged in partnership-based projects that are pivotal in fostering information and knowledge transfer and technology at the secondary level. Another method used was a document review of records on the country’s university-school partnerships. The study found that Tanzania’s universities and schools work collaboratively to execute their core functions and enhance equity, inclusion, and quality education, aligning with institutional, national, and international goals that are fundamental to sharing information, knowledge, and technology for optimal results. Overall, the study found that university-school partnerships in the country extend beyond promoting practical training for pre-service teachers, supporting professional development, and enhancing teaching and learning through the sharing of information and knowledge. Moreover, these partnerships contribute to technological development, innovation, job creation, and the resolution of practical problems in the education sector through enhanced information and knowledge exchange. Overall, university-school partnerships are crucial in institutional and individual well-being; hence, they are worth sustaining through comprehensive policies and improved practices. https://dx.doi.org/10.4314/udslj.v20i1.12